2022
DOI: 10.1021/acsnano.1c09925
|View full text |Cite
|
Sign up to set email alerts
|

Ti3C2Tx MXene-Based Flexible Piezoresistive Physical Sensors

Abstract: MXenes have received increasing attention due to their twodimensional layered structure, high conductivity, hydrophilicity, and large specific surface area. Because of these distinctive advantages, MXenes are considered as very competitive pressure-sensitive materials in applications of flexible piezoresistive sensors. This work reviews the preparation methods, basic properties, and assembly methods of MXenes and their recent developments in piezoresistive sensor applications. The recent developments of MXene-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
117
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 263 publications
(117 citation statements)
references
References 194 publications
0
117
0
Order By: Relevance
“…A diagrammatic illustration of the simplified sensing model of the O‐MXene‐based piezoresistive sensor is shown in Figure S12. The most important factor affecting the sensitivity of piezoresistive sensors is the change in the contact resistance caused by deformation under applied pressure 34 . The total resistance can be expressed as R sensor = R MXene + R electrode + R contact , where R MXene is the resistance of the MXene‐based sensing element, R electrode is the resistance of the interdigital electrode, and R contact is the contact resistance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A diagrammatic illustration of the simplified sensing model of the O‐MXene‐based piezoresistive sensor is shown in Figure S12. The most important factor affecting the sensitivity of piezoresistive sensors is the change in the contact resistance caused by deformation under applied pressure 34 . The total resistance can be expressed as R sensor = R MXene + R electrode + R contact , where R MXene is the resistance of the MXene‐based sensing element, R electrode is the resistance of the interdigital electrode, and R contact is the contact resistance.…”
Section: Resultsmentioning
confidence: 99%
“…The most important factor affecting the sensitivity of piezoresistive sensors is the change in the contact resistance caused by deformation under applied pressure. 34 The total resistance can be expressed as R sensor = R MXene + R electrode + R contact , where R MXene is the resistance of the MXene-based sensing element, R electrode is the resistance of the interdigital electrode, and R contact is the contact resistance. In the initial state without compression, the fibrous structure of the sensor was loose, and the interlayer spacing of the MXene nanosheets was relatively large, thereby resulting in a small contact area and large contact resistance (Figure S12A).…”
Section: Materials and Device Characterizationmentioning
confidence: 99%
“…31 For zero-dimensional and one-dimensional materials, because of the small specific surface area, the bonding with the matrix is often not strong enough, which results in a poor stability. In contrast, two-dimensional (2D) materials, such as graphene, MXene, 33,34 and MoS 2 , 35 usually have a larger specific surface area; thus they are more favored by researchers. For instance, Ma et al fabricated a conductive reduced graphene oxide (rGO) fiber and further sew it into Taekwondo suits to monitor double tactile and tension movement in real time.…”
Section: ■ Introductionmentioning
confidence: 99%
“…On the other hand, for the fabrication of wearable electronic devices, the most commonly used method today is to combine fibers or fabrics, which are inherently nonconductive, with conductive active materials such as metal nanoparticles and nanowires, , carbon-based materials, , and conductive polymers. , For zero-dimensional and one-dimensional materials, because of the small specific surface area, the bonding with the matrix is often not strong enough, which results in a poor stability. In contrast, two-dimensional (2D) materials, such as graphene, MXene, , and MoS 2 , usually have a larger specific surface area; thus they are more favored by researchers. For instance, Ma et al fabricated a conductive reduced graphene oxide (rGO) fiber and further sew it into Taekwondo suits to monitor double tactile and tension movement in real time .…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] MXenes have high specific surface area and amount of surface termination groups which can be introduced during etching process, such as -O, -F, or -OH termination groups. [12][13][14][15] Researchers have modified MXene under different conditions such as synthetic MXene/rGO/PS spheres [16] or MXene/rGO foams [17] applying electric field and mechanical strain [18][19][20] to fabricate high-sensitivity pressure sensors. Wu et al experimentally and theoretically showed that Ti 3 C 2 MXene can be used for various gases (methane, hydrogen sulfide, water, ammonia, NO, ethanol, methanol, and acetone) sensing.…”
Section: Introductionmentioning
confidence: 99%